Authority Of Bawaslu In Election Law Enforcement And Justice (Analysis Of Handling Of Election Administrative Violations Through Adjudication) - Khoirudin; Imam Budi Santoso; Pri Pambudi Teguh (IHSA Institute, 2021)
One indicator of a democratic rule of law is general elections to ensure the sovereignty of the people, democratic elections are elections that run in accordance with the electoral legal framework. The implementation of elections has its own legal character, different from other laws, therefore, the legal framework for elections must be able to guarantee the rights of the people in elections, so that law enforcement and election justice can run upright and straight, leading to elections with integrity. In the electoral legal framework, Bawaslu is given more authority by the election law, in addition to being tasked with prevention and supervision, it is also given adjudication authority in resolving the process of handling election administrative violations. The research method that the author uses is normative juridical, primary, secondary and tertiary legal data sources, data collected through library studies and field studies, and analyzed by qualitative juridical. The results of the study show that the authority of Bawaslu in enforcing election law and justice is to take legal action in the election process if it is not in accordance with the election laws and regulations. Such legal actions can be constructive, namely law enforcement that allows to change and/or cancel decisions, and can be punitive, namely those that allow sanctions to be imposed on perpetrators of violations, the decisions issued by Bawaslu are binding on the parties. The Bawaslu adjudication mechanism is guided by Perbawaslu concerning the Settlement of Election Administrative Violations. KPU is obliged to follow up on Bawaslu's decision. If it is not followed up, the KPU can be reported to the DKPP, for violating the election organizer's code of ethics.